Underwriter's Reputation - An Appropriate Risk Proxy For IPO? - Ng, Siok Khim (2005)
This study analyses the co-relationship of a few ex-ante uncertainty factors on the under-pricing of Initial Public Offerings in Malaysia. As an extension to the main study, several other risk proxies have been studied.